Green Innovations and Consumer Purchase Behavior: A Systematic Literature Review - Chynthia Noura Elysha; Shelli Melita; Yoestini (LifeSciFi, 2025)
The increasing environmental awareness among consumers has encouraged companies to adopt sustainable innovation strategies. In this context, green innovation has emerged as a key approach to foster consumers’ intention to purchase eco-friendly products (green purchase intention). This study aims to systematically examine the relationship between green innovation and green purchase intention using a Systematic Literature Review (SLR) method. A total of 21 peer-reviewed articles published in reputable journals between 2019 and 2025 were analyzed qualitatively based on topic relevance, research methodology, and key findings. The results indicate that the implementation of green innovation strategies consistently exerts a positive influence on consumers’ green purchase intention. These findings highlight the critical role of green innovation not only in product development but also in marketing strategies aligned with consumers’ environmental values. This study offers both theoretical and practical insights for companies and researchers in designing environmentally responsible business strategies that enhance competitiveness in markets increasingly driven by sustainability concerns.